True sisters - Dallas, Sandra (St. Martin's Press, 2012)
1856. Mormon converts Nannie, Louisa, Jessie, and Anne, all from the British Isles, travel in the Martin Handcart Company, making the 1,300-mile journey on foot from Iowa City to Salt Lake City, while enduring unimaginable hardships. Each woman will test the boundaries of her faith and learn the true meaning of survival and friendship along the way.